What factors affect the employee's performance at the Ministry of Religion in Kalimantan? - Misra, Isra; Sadikin, Ali; Sholehudin, Muhammad (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2023)
The exogenous variables in this study are competence and organizational culture, and the endogenous variable is the employee’s performance at the Ministry of Religion of the Republic of Indonesia in Kalimantan region. We sampled 99 staff in all work units of the Ministry of Religion in Kalimantan. The data for this study were collected through a questionnaire followed by interviews. The researchers chose mixed methods as their research approach. The data was then analyzed using SEM PLS, which consisted of descriptive statistical tests, inferential statistics, outer and inner models, path plots, and hypothesis testing. The results showed that competence had no significant effect on performance but had a significant positive effect on organizational commitment. Furthermore, organizational culture significantly affects team member performance, while organizational engagement does not. Organizational involvement has a large positive effect on team member performance. In other words, organizational commitment can convey team member competence and performance, but organizational commitment fails to convey thisAbstrakVariabel eksogen dalam penelitian ini adalah kompetensi dan budaya organisasi, dan variabel endogen adalah prestasi pejabat Kementerian Agama Republik Indonesia di wilayah Kalimantan. Penelitian ini merupakan penelitian kuantitatif dengan sampel terhadap 99 pegawai di seluruh unit kerja Kementerian Agama di Kalimantan. Data untuk penelitian ini dikumpulkan melalui kuesioner yang dilanjutkan dengan wawancara. Para peneliti memilih metode campuran sebagai pendekatan penelitian ini. Data tersebut kemudian dianalisis menggunakan SEM PLS yang terdiri dari uji statistik deskriptif, statistik inferensial, outer dan inner model, path plot, dan pengujian hipotesis. Hasil penelitian menunjukkan bahwa kompetensi tidak berpengaruh signifikan terhadap kinerja, tetapi berpengaruh positif signifikan terhadap komitmen organisasi. Selanjutnya budaya organisasi berpengaruh signifikan terhadap kinerja karyawan, sedangkan keterikatan organisasi tidak berpengaruh. Keterlibatan organisasi berpengaruh positif besar terhadap kinerja karyawan. Dengan kata lain, komitmen organisasi dapat menyampaikan kompetensi dan kinerja karyawan, tetapi komitmen organisasi gagal untuk menyampaikan hal ini